Enhancing High School Spectroscopy Education: The Efficacy of a Virtual Reality Laboratory for Hydrogen Emission Experiments - Melani Putria Dewi Sari; Hartono Bancong; Rahmawati Rahmawati (Jurnal Pendidikan MIPA, 2026)
Many high schools struggle to conduct a hydrogen emission spectrum experiment because they lack sufficient, up-to-date, and easy-to-use optical equipment. As a result, students often miss opportunities to observe diffraction patterns and to connect their analyses to atomic transitions. This study developed a virtual-reality-based laboratory for a hydrogen emission spectrum experiment to measure the spectrum across different diffraction orders and to improve students' learning outcomes. The ADDIE framework was used for the research and development process. It included analysis, design, development, implementation, and evaluation. Four physics teachers were interviewed to identify classroom problems and users' needs. The virtual reality-based laboratory made a hydrogen light source, a spectrometer, and a diffraction grating that users could interact with to align and measure angles for data collection. Three experts used a Likert-scale tool to rate its validity with respect to scientific accuracy, instructional design, and ease of use. Used Aiken's V to check for validity. The simulations showed that the diffraction patterns were always the same. The average angle changed from violet to red, and the second-order angle was always higher than the first-order angle for the same color. The first- and second-order wavelength estimates were very close to each other (3.80×10⁻⁷–6.20×10⁻⁷ m), and 97–98% of the colors measured were the same in all orders. The values we found for the constants were very close to the known values (Rydberg constant 1.096×10⁷ m⁻¹, error 0.09%; Planck constant 6.663×10⁻³⁴ J s, error 0.56%). Validator coefficients (0.80–0.90) helped improve things, such as a phased rollout, a zoomable angular scale, feedback on alignment, and smoother interactions with the controller. The learning outcomes improvement, measured using the normalized gain index (N-Gain), was N-Gain = 0.83 (83.11%). This shows that the development of media has improved students' learning outcomes. Virtual reality laboratories are more accessible and help students learn more about spectroscopy. Keywords: diffraction grating simulation; hydrogen emission spectrum; physics education; spectroscopy experiment; virtual reality laboratory.